Giant Occipitocervical Lipomas: Evaluation with Two Cases - Basmaci, Mehmet (Medknow Publications & Media Pvt Ltd, 2012)
Lipomas are capsulated benign tumours that are commonly found in all body parts. A lipoma is a well-defined mesenchymal tumour that arises from the adipose tissue. Although giant lipomas are rare in the head and neck regions, when they are located here, they are most commonly found in the subcutaneous posterior neck area. Recurrence as well as invasion is very rare after total surgical excision. In this article, we present two rare cases of giant lipomas in the posterior occipitocervical region, which is an exceptional location.